Antibacterial and Antialgae Activities and Antifouling Capability of Dithiodipropionamide Derivatives - Cong, W.W.; Yu, L.M.; Wang, Q. (Asian Journal of Chemistry, 2010)
Before, the potential property of dithiodipropionamide derivatives were ignored, as the intermediate material of isothiazolones, which were good material in terms of antibacteria, inhibition of algae and antifouling. Here we select three dithiodipropionamide derivatives and studied their capabilities of antibacteria, inhibition of algae and antifouling activity. And taking N,N'-dibutoxymethyl- dithiodipropionamide (BMD) as an example, we obtained that the minimal inhibitory concentration (MIC) of BMD for Staphylococcus aureus, Escherichia coli and Fission yeast were 0.1250, 0.2500 and 0.1250 mg/mL, respectively. The LC50 value of BMD were 1.64 and 1.39 mg/L for Dicrateria zhanjiangensis at 24 and 48 h correspondingly. Meanwhile we used these three dithiodipropionamide derivatives as antifouling agents in antifouling paint to make test panels, then, immersed test panels in the sea for more than 5 months, resultly, test panels were covered with only a little macroorganism. Thus, the three compounds have potential value as antifoulants.